L'Amérique septentrionale et les Peaux-Rouges [ressource électronique] : explorations, impressions de voyage, scènes de moeurs indigènes - Vattemare, H. (Hippolyte), m. 1882.; Möllhausen, Balduin 1825-1905. Tagebuch einer reise vom Mississippi nach den küsten der Südsee.; Milton, William Fitzwilliam, Viscount, 1839-1877. The North-west passage by land.; Catlin, George, 1796-1872. Letters and notes on the manners, customs, and conditions of the North American Indians. (Paris : Librairie Hachette, 1881)
Abrégé de trois ouvrages: The Northwest passage by land / Viscount Milton et W.B. Cheadle; Tagebuch einer reise vom Mississippi nach den kü sten der Südsee / von Balduin Möllhausen; et Letters and notes on the manners, customs and conditions of the North American Indians / by George Catlin. Comprend des références bibliographiques. Reproduction électronique. Mode of access: Internet. Mode d'accès: World Wide Web. 44